(untitled) (Annual of the Faculty of Philosophy in Skopje, 2024)
The UN Convention on the Rights of Persons with Disabilities (CRPD) with its Optional Protocol is the first binding legal act and leading international instrument regarding the rights of persons with disabilities. One of the principles of CRPD is “respect for inherent dignity, individual autonomy including the freedom to make one’s own choices and independence”, whereby persons with disabilities are recognized as holders of rights taking into account their specific situation. CRPD recognizes in Article 6 that “women and girls with disabilities are subject to multiple discrimination” and mandates signatory countries to “take measures to ensure their full and equal enjoyment of all human rights and fundamental freedoms.” The research was done in order to examine the readiness of the state to institutionally cover the awareness of girls and women with disabilities, their education on the issue of violence, access to services and information appropriate to the needs of each category separately, as well as systemic solutions for their protection from violence. A qualitative research strategy was applied, and the research was conducted with representatives of the Centers for Social Work, representatives from the Ministry of Labor and Social Policy, professionals who are direct providers of services in the field of non-family protection, as well as the girls and women with disabilities themselves. The main conclusions that emerge from the research say that girls and women with disabilities are more susceptible to violence, especially by their partners or family members. More awareness is needed to recognize and encourage reporting of violence.